Clinical significance of blood platelets and mean platelet volume in patients with ulcerative colitis - Zhitao Chen; Yaqi Lu; Jie Wu; Heng Zhang (Journal of International Medical Research, 2021)
Objectives This retrospective study aimed to investigate and analyze the clinical significance of blood platelets (PLTs) and mean platelet volume (MPV) in patients with ulcerative colitis (UC). Methods A total of 132 patients with UC and 208 healthy subjects were enrolled. PLTs, MPV, platelet-large cell rate (P-LCR), C-reactive protein (CRP), fibrinogen (FIB) and D-dimer were analyzed. Correlations were calculated between disease activity/extent of disease and MPV, PLT, and CRP levels in patients with UC. Results PLT levels were significantly higher while MPV and P-LCR were lower in patients with UC compared with controls. Disease activity was positive correlated with CRP (r = 0.564) and PLT (r = 0.307) but negatively correlated with MPV (r = −0.351). Extent of disease was positively correlated with CRP (r = 0.312) but showed no correlation with PLTs and MPV. FIB and D-dimer were higher in patients with UC, but the difference in FIB levels was not statistically significant. Conclusions PLTs and MPV are potential biomarkers for UC disease activity. These data may help clinicians to attain a more comprehensive judgment of the general condition of patients with UC.